2020
DOI: 10.1088/1361-6587/aba768
|View full text |Cite
|
Sign up to set email alerts
|

Simulation studies of the radiation-driven tearing mode in tokamaks

Abstract: The influence of bremsstrahlung and cyclotron radiation on the evolution and saturation of the m/n = 2/1 resistive tearing mode is investigated by using a three-dimensional toroidal magnetohydrodynamic code. It is found that accumulation of impurities (such as tungsten) in magnetic islands has a destabilizing effect on the tearing mode due to an imbalance of local radiative cooling and Ohmic heating inside the island. The asymmetry current effect and the nonlinear mode coupling play an important role on evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In those pulses a sequence of TM with increasing safety factor (5/4 → 4/3 → 3/2 → 2/1) clearly show the consequence of an evolving q-profile [4,5]. Whereas the impurity radiation and the induced TM are widely believed to play key roles in the disruption process, the exact mechanism underlying the impurity radiation and TM interaction, as well as its universal nature in connection to the disruption, remains a subject of fundamental interests and continued research [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those pulses a sequence of TM with increasing safety factor (5/4 → 4/3 → 3/2 → 2/1) clearly show the consequence of an evolving q-profile [4,5]. Whereas the impurity radiation and the induced TM are widely believed to play key roles in the disruption process, the exact mechanism underlying the impurity radiation and TM interaction, as well as its universal nature in connection to the disruption, remains a subject of fundamental interests and continued research [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The thermo-resistive TM theory was further formally refined and extended to construct a model for the Greenwald density limit [11][12][13][14][15][16]. Recent MHD simulations have demonstrated the impurity radiation effects on the magnetic island that are consistent with the thermal-resistive TM theory [17,18]. However, those simulation findings rely on the preexisting small islands that initially grow from the linear tearing unstable equilibrium profile where the TM asymptotic matching parameter ∆ ′ > 0.…”
Section: Introductionmentioning
confidence: 99%
“…(The accumulation of Mo and Fe can be judged from the signal of MoXXXII, FeXXIII, FeXVIII, soft x-ray (SXR) and large Z eff (> 3).) Although this W accumulation is not as serious as the last one, but at about 4.7 s, the simultaneous accumulation of multiple heavy impurity species may lead to the high β N collapse by triggering to the tearing mode (TM) due to the resistivity and radiation increase [70][71][72][73][74][75] as shown in figure 3. The concentration of these heavy impurities diagnosed by extreme ultra violet [76] is illustrated in figure 4.…”
Section: East Hybrid Discharge With Itbmentioning
confidence: 97%
“…Such studies on plasma radiation have been carried out, including bremsstrahlung, recombination radiation, cyclotron radiation and line radiation. [16,[26][27][28][29][30][31][32][33][34] It is worth mentioning that the line radiation comes mainly from the impurity radiation in the tokamak plasmas. Gates et al found that islands could be driven by the plasma radiation and this performance was consistent with the density limit.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are still some unknown issues regarding the effects of plasma radiation on NTMs. [16,32,34] On the other hand, reversed magnetic shear (RMS) configuration, as one of the main schemes in the experimental scenarios, is most likely to achieve the long-pulse steadystate operation for the toroidal fusion devices. [1,6,8,10,11,[35][36][37][38][39][40][41][42][43][44][45][46] In the RMS configuration, the internal transport barrier can be triggered so that the core plasma pressure has a high gradient and then generates a high fraction of bootstrap current, which is recognized to be the steady-state configuration for the advanced tokamaks.…”
Section: Introductionmentioning
confidence: 99%